Safety assessment of the process ‘Gneuss 2’, based on Gneuss technology, used to recycle post-consumer PET into food contact materials - EFSA Panel on Food Contact Materials, Enzymes, Flavourings and Processing Aids (CEF) (2021)
This scientific opinion of the EFSA Panel on Food Contact Materials, Enzymes, Flavourings and Processing Aids deals with the safety evaluation of the recycling process Gneuss 2 (EU register No RECYC0144). The input is washed and dried poly(ethylene terephthalate) (PET) flakes originating from collected post-consumer PET containers, containing no more than 5% of PET from non-food applications. They are extruded under vacuum into pellets or sheets. Having examined the challenge test provided, the Panel concluded that the decontamination in the extruder under vacuum degassing is the critical step for the decontamination efficiency of the process. The operating parameters to control its performance are well defined and are temperature, pressure, residence time, throughput rate, the rotor speed and the satellite screws speed. The operating parameters of this step are at least as severe as those obtained from the challenge test. It was demonstrated that this recycling process is able to ensure that the level of migration of potential unknown contaminants into food is below a conservatively modelled migration of 0.1 μg/kg food. Therefore, the recycled PET obtained from the process Gneuss 2 intended for the manufacture of articles made with up to 90% recycled post-consumer PET and intended for contact for long-term storage at room temperature with all types of foodstuffs is not considered of safety concern. Trays made of this recycled PET are not intended to be used, and should not be used, in microwave and conventional ovens.